Rhinology Fellowship Training and its Scholarly Impact. Issue 5 (September 2013) - Svider, Peter F.; Blake, Danielle M.; Setzen, Michael; Folbe, Adam J.; Baredes, Soly; Eloy, Jean Anderson
Background: Previous examination of the impact of fellowship training on scholarly productivity among otolaryngologists found that head and neck surgeons and otologists had a higher mean h–index than fellowship-trained rhinologists. Because fellowship training in rhinology is a historically newer trend, the objectives of the present analysis were to further characterize research productivity among fellowship-trained academic rhinologists, including geographic and temporal trends, to gain insight into the future direction of scholarly pursuits within the field. Methods: Fellowship-trained rhinologists in academic practices were identified from the American Rhinologic Society online listings and organized by academic rank, number of years in practice, location, and h-index, as calculated using the Scopus database. Results: Mean h-index rose with increasing years in practice after fellowship. The h-index, number of publications, and the E-factor (a newly described bibliometric) increased with successive academic rank. The E-factor for rhinologists in this current analysis was not statistically different from the values calculated for other otolaryngology subspecialties (p > 0.05). Conclusion: Fellowship-training in rhinology is a relatively recent development, with half of the academic rhinologists included in this analysis having completed fellowship training within the past 5 years. Scholarly productivity among academic rhinologists increases with academic seniority. As the current cohort of fellowship-trained rhinologists progress in their academic careers, previously described deficits in scholarly productivity relative to other subspecialties are expected to diminish.